The Utilization of Artificial Intelligence in Arabic Language Learning: between Linguistic Competence and Islamic Spirituality - Dahlan, Juwairiyah; abdurrahman, muzakki; Rif'at, Ahmad Dzulkifli (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This study discusses the revolution of Arabic language learning in the digital era, focusing on the role of Artificial Intelligence (AI) in enhancing language competence while fostering spiritual intelligence. Using a library research method, this study reviews recent literature (2020–2023) on the application of AI in language learning and Islamic education. The findings reveal that AI provides adaptive, interactive, and data-driven learning that strengthens the four core Arabic language skills (listening, speaking, reading, and writing), including specific aspects such as nahwu, sharaf, and phonetics. Furthermore, AI has the potential to support the integration of Islamic values through features such as prayer reminders, Qur’anic verses, and the internalization of learning ethics. This research highlights that AI should not be regarded merely as a technical tool but as a medium of technological spiritualization that combines intellectual competence with the cultivation of Islamic character and morality. The contribution of this article is to provide an integrative perspective on how AI can be utilized not only to strengthen Arabic linguistic competence but also as a medium for fostering Islamic spirituality within the context of education.